Improving Scientific Argumentation Through The Hierarchy Of Inquiry - Probosari, Riezky Maya; Ramli, Murni; *, Sajidan (Sebelas Maret University, 2016)
This study examined how studentsâ scientific argumentation changed over as they participated in hierarchy ofÂ inquiry learning. The hierarchy of inquiry is a comprehensive approach in which students working for anextended period of time that integrated several ways of inquiry systematically to investigate and respond to aÂ complex question, problem, or challenge. This action research was conducted in Biology Teacher EducationÂ Program Faculty of Teacher Training and Education Sebelas Maret University. The students, who were at theÂ 4rd semester and who studied the class of Plant Embryology, were purposely selected. The data wereÂ collected from interviews with the researchers, classroom observations, and collection of student portfolios.Â The scientific argumentation was measured using modified Toulminâs Argument Pattern (TAP) with fourÂ kinds of argument elements: claim, evidence, reasoning, and rebuttal which presented in oral and written.Â The results showed that students who experienced with the hierarchy of inquiry performed better scientificÂ argumentation which reflecting their higher-order thinking abilities. We conclude that hierarchy ofÂ inquiry is possible in fostering studentâs scientific argumentation, doing some inquiry activities, and thusÂ make a positive impact on scientific argumentation ability . The findings can be helpful in the process ofÂ designing the new curricula for teacher candidates in order to foster scientific inquiry.